Assessing the Contribution of Sustainable Agriculture, Rural Infrastructure, and Cooperative Development to Livelihood Improvement in Rural Indonesia - Haryono, Haryono (West Science Journal Economic and Entrepreneurship, 2025)
This study investigates the contribution of sustainable agriculture, rural infrastructure, and cooperative development to livelihood improvement in rural Indonesia. Using a quantitative approach, data were collected from 255 rural respondents through a structured questionnaire measured on a five-point Likert scale. The analysis was conducted using Structural Equation Modeling–Partial Least Squares (SEM-PLS 3). The descriptive findings indicate that all three constructs scored relatively high, with sustainable agriculture averaging 3.92, rural infrastructure 3.85, cooperative development 3.88, and livelihood improvement 3.95. Measurement model results confirm the reliability and validity of the instruments, with Cronbach’s alpha values exceeding 0.80, composite reliability above 0.85, and average variance extracted (AVE) surpassing the 0.50 threshold. Structural model results reveal that sustainable agriculture (β = 0.34, p < 0.01), rural infrastructure (β = 0.28, p < 0.05), and cooperative development (β = 0.26, p < 0.05) all significantly contribute to livelihood improvement. Among these, sustainable agriculture demonstrates the strongest effect, suggesting its critical role in ensuring food security, environmental sustainability, and economic resilience in rural communities. These findings highlight the importance of integrating sustainable farming practices, infrastructure expansion, and cooperative institutions as a comprehensive policy framework for rural development in Indonesia.